Biocatalytic route scouting and enzyme screening toward the synthesis of α-benzyl L-glutamate - Quaedflieg, Peter J. L. M.; Jente, Lisanne M. H.; Müller, Monika; Vermote, Linda; Plesciuc, Victor; van der Laan, Jan-Metske; Nielsen, Lone; Schürmann, Martin (Frontiers in Catalysis, 2024)
We here report four biocatalytic approaches for the synthesis of the protected amino acid building block α-benzyl L-glutamate. Screenings of these routes to identify active and selective enzymes were conducted, and major hits were confirmed in retest reactions. In the first approach N-Boc L-glutamic acid is mono-benzylesterified by the protease Alcalase with 81% yield; and in the other three approaches, a biocatalytic γ-selective hydrolysis of α,γ-dibenzyl Lglutamate, α-benzyl L-glutamine, and α-benzyl L-pyroglutamate is performed in up to 71% yield.